High-temperature methanol steam reforming catalyst
By developing a catalyst based on the zinc-aluminum spinel phase, the problems of catalyst activity and stability in methanol steam reforming reaction at high temperatures are solved, and efficient, low-cost and environmentally friendly hydrogen production is achieved.
Patent Information
- Application Number
- CN202380040236.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-09
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-14
AI Technical Summary
The lack of a cost-effective and environmentally friendly methanol steam reforming catalyst that is active and stable under high temperature conditions in the prior art has limited the efficiency and safety of methanol steam reforming reaction.
A catalyst based on zinc-aluminum spinel phase was developed, containing 20-75% ZnO phase, 20-60% zinc-aluminum spinel phase and 0.1-20% Cu dopant by preparation method It includes precipitation and calcination of precursor aqueous solutions of zinc, aluminum and copper to form a catalyst composition with high activity.
The catalyst composition exhibits high methanol conversion and hydrogen selectivity at high temperatures, and has good stability, avoids the use of chromium, reduces production costs, and improves reaction efficiency.
Smart Images

Figure CN119317483A_ABST
Abstract
Description
[0001] Public background Public domain
[0002] The present disclosure relates generally to methanol steam reforming catalyst materials. More specifically, the present disclosure relates to spinel-based catalysts useful in high temperature methanol steam reforming reactions, to methods of making such catalysts, and to methods of forming hydrogen from methanol using such catalysts. Technical Background
[0003] Hydrogen fuel cells are one of the most promising new clean technologies for power generation. The technology is currently attracting increasing attention due to its energy efficiency and environmental benefits. However, storage and transportation of hydrogen remain challenging due to insufficient storage capacity and safety issues. Therefore, there is a need for alternative sources of hydrogen that overcome these storage and transportation issues.
[0004] One such alternative is to use methanol to produce hydrogen on site through methanol steam reforming. Methanol steam reforming can reduce or even eliminate the necessity of hydrogen storage and transportation operations. Compared with hydrogen, methanol storage and transportation are much more cost-effective and much safer. Compared with methane and other alcohols, methanol is also a desired precursor candidate for hydrogen production. It has a high hydrogen content, which theoretically results in three moles of hydrogen being produced by one mole of methanol during steam reforming. And finally, methanol can be produced from biomass, which greatly reduces carbon footprint, making the methanol steam reforming method more environmentally sustainable. Therefore, methanol steam reforming provides an alternative for providing a desired hydrogen to fuel cells used in fixed power systems and mobile applications.
[0005] Methanol steam reforming is conventionally operated either at low temperatures (less than 300° C.) or high temperatures (at least 300° C.). Because the reaction is endothermic (Equation 1), the reforming reaction may desirably be run at higher temperatures to achieve higher H2 yields.
[0006] CH3OH + H2O 3H2+ CO2, ΔH 298K = 49.3 kJ / mol (1)
[0007] H2 selectivity has been reported to reach 75% under favorable conditions. Therefore, it is advantageous to have a methanol steam reforming catalyst that can withstand high temperature conditions to achieve high methanol conversion. Of course, steam reforming processes require catalysts that are suitable for their specific conditions, which is a particularly stringent requirement for high temperature processes.
[0008] Various catalysts have been developed to adapt to specific methanol steam reforming reaction conditions. Conventionally, the most common catalysts used in methanol steam reforming and methanol synthesis are based on copper and metals from Group VIIIB (see, for example, Chem. Rev. 2007, 107, 3992-4021). Copper-based catalysts are not only active and selective to H2, but also stable at reaction temperatures below 300°C. However, copper catalysts, such as commercially available CuO-ZnO / Al2O3 catalysts, tend to sinter rapidly at temperatures exceeding 280°C and are highly sensitive to condensed steam, sulfur and chlorides, and coke deposition. Their autoignition characteristics are also problematic when exposed to air. In order to address these problems, rare earth oxides, Cr2O3 and ZrO2 have been used as carriers or support materials to improve the dispersion of copper active materials and reduce sintering during the reaction. Another common approach to improve the CuO-ZnO catalyst formulation is to add promoters, such as Ce, La, Ba, Mg, Co, Fe, etc. (see, e.g., EP1077081A2, CN104741128, JP2003265961A).
[0009] Unlike copper-based catalysts, palladium / zinc or platinum / zinc alloy catalysts tend to be more stable at high temperatures (e.g., >350°C), but show relatively low activity. Coupled with the high price of precious metal costs, palladium / zinc or platinum / zinc catalysts have much lower potential in commercial applications (see, for example, WO2010138483A2). U.S. Patent Application Publication Nos. 2001 / 0021469A1 and 2002 / 0039965A1 report that PdZnZr and Pd / Pt-CuZn catalysts also suffer from deactivation at high temperatures, and zinc leaching is observed in PdZnZr catalysts during reforming. Another category of common high-temperature methanol steam reforming catalysts is chromium / zinc catalysts. They show excellent activity, selectivity and stability at elevated temperatures. However, as countries around the world increase their environmental protection efforts, the toxicity and carcinogenicity of chromium make these catalysts increasingly undesirable for industrial use. Other catalysts such as CuZr, NiZr, AgY, NiZn, AuHf, etc. have been used for low temperature applications but are not suitable for high temperature reforming reactions (see, for example, US5635439A).
[0010] Therefore, there remains a need for a methanol steam reforming catalyst that is active at high temperatures and that is sustainable, cost-effective and environmentally friendly. The inventors of the present application have developed a methanol reforming catalyst that maintains its catalytic activity while operating at high temperatures.
[0011] Overview
[0012] The inventors of the present application have determined that a catalyst based on a zinc-aluminum spinel phase with a small amount of copper dopant can provide high temperature activity and stability at low cost and without the negative environmental impact of using large amounts of chromium. Therefore, one aspect of the disclosure provides a methanol reforming catalyst composition comprising:
[0013] A ZnO phase, present in the composition in an amount of 20-75 wt %;
[0014] a zinc-aluminum spinel phase, present in the composition in an amount of 20-60% by weight; and
[0015] The Cu dopant is present in the composition in an amount of 0.1-20 wt %.
[0016] In various embodiments, the catalyst composition has little to no crystalline Al2O3 phase.
[0017] Another aspect of the present disclosure provides a calcined methanol reforming catalyst composition comprising: oxides of Zn, Al and Cu, wherein:
[0018] Zn is present in the composition in a total amount of 40-80 wt % (e.g., 60-80 wt %), calculated as ZnO;
[0019] Al is present in the composition in a total amount of 20-50 wt % (e.g., 20-40 wt %), calculated as Al2O3; and
[0020] Cu is present in the composition in a total amount of 0.5-25 wt % (e.g., 1-15 wt %), calculated as CuO,
[0021] wherein the catalyst composition comprises at least 20 wt % (e.g., at least 30 wt %, or at least 40 wt %) zinc-aluminum spinel as determined by XRD and calculated as ZnAl2O4.
[0022] Another aspect of the present disclosure provides a method for preparing the methanol reforming catalyst composition described herein. The method includes:
[0023] providing a precursor aqueous solution comprising zinc ions, aluminum ions and copper ions;
[0024] precipitating a solid catalyst precursor comprising zinc, aluminum and copper salts from the aqueous precursor solution; and then
[0025] The solid catalyst precursor is calcined to provide a catalyst composition.
[0026] Another aspect of the present disclosure provides a method of conducting a methanol reforming reaction comprising contacting a feed comprising water and methanol with a methanol reforming catalyst composition described herein at a temperature of at least 300°C to form hydrogen and carbon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The methanol conversion, hydrogen selectivity, carbon monoxide selectivity and carbon dioxide selectivity of the catalysts described herein are illustrated as a function of the duration of the test.
[0028] Figure 2 is a graph of X-ray diffraction (XRD) patterns of certain materials described herein.
[0029] Detailed Description
[0030] The present disclosure relates to methanol reforming catalyst compositions comprising zinc, aluminum, oxygen and copper. The present disclosure shows that such catalysts, which may advantageously be substantially free of chromium, may exhibit activity comparable to or greater than conventional methanol reforming catalysts. The present disclosure shows that such catalysts may, in various embodiments, operate at higher temperatures than catalysts prepared according to conventional methods.
[0031] In various advantageous aspects and embodiments of the compositions described herein, zinc is present in the form of ZnO. In various advantageous aspects and embodiments of the compositions described herein, zinc, aluminum, and oxygen together form a zinc-aluminum spinel crystal structure. Advantageously, the inventors of the present application have determined that incorporating copper into a methanol reforming catalyst can provide improved catalyst activity. Therefore, in various embodiments described herein, the material of the disclosure includes a Cu dopant. The inventors of the present application have determined that including copper can advantageously provide good catalytic activity and stability at high temperatures.
[0032] Therefore, one aspect of the disclosure is a methanol reforming catalyst composition. The catalyst composition comprises a ZnO phase present in an amount of 20-75 wt %, a zinc-aluminum spinel phase present in the composition in an amount of 20-60 wt %, and a Cu dopant present in the composition in an amount of 0.1-20 wt %. The amount of such phases is determined using a Littlefield refinement method using X-ray diffraction.
[0033] As noted above, ZnO is present in the composition of this aspect with an amount in the range of 20-75 % by weight. The amount of ZnO in the catalyst composition of the disclosure can be changed within this range. For example, in the various embodiments described in addition herein, ZnO is present in an amount in the range of 20-70 % by weight, for example, 20-65 % by weight, or 20-60 % by weight, or 20-55 % by weight, or 20-50 % by weight, or 20-45 % by weight, or 20-40 % by weight. In the various embodiments described in addition herein, ZnO is present in an amount in the range of 25-75 % by weight, for example, 25-70 % by weight, or 25-65 % by weight, or 25-60 % by weight, or 25-55 % by weight, or 25-50 % by weight, or 25-45 % by weight, or 25-40 % by weight. In various embodiments described herein in addition, the ZnO phase is present in the composition in an amount in the range of 30-75% by weight, or 30-70% by weight, or 30-65% by weight, or 30-60% by weight, or 30-55% by weight, or 30-50% by weight, or 30-45% by weight, or 30-40% by weight. In various embodiments described herein in addition, the ZnO phase is present in the composition in an amount in the range of 35-75% by weight, for example, 35-70% by weight, or 35-65% by weight, or 35-60% by weight, or 35-55% by weight, or 35-50% by weight, or 35-45% by weight, or 35-40% by weight. In various embodiments described herein in addition, the ZnO phase is present in the composition in an amount in the range of 40-75% by weight, for example, 40-70% by weight, or 40-65% by weight, or 40-60% by weight, or 40-55% by weight, or 40-50% by weight.
[0034] In various embodiments described in addition herein, the ZnO phase in the composition described in addition herein has an average grain size of 1-50 nm. For example, in various embodiments, the ZnO phase has an average grain size of 1-45 nm, for example, 1-40 nm, or 1-35 nm, or 1-30 nm. In various embodiments, the ZnO phase has an average grain size of 2-50 nm, for example, 2-45 nm, or 2-40 nm, or 2-35 nm, or 2-30 nm. In various embodiments, the ZnO phase has an average grain size of 5-50 nm, for example, 5-45 nm, or 5-40 nm, or 5-35 nm, or 5-30 nm. Those skilled in the art will appreciate that smaller grain size corresponds to higher surface area. Having a higher surface area provides a larger total catalytic area for the occurrence of methanol steam reforming reaction, resulting in generally higher catalytic activity.
[0035] As noted above, the zinc-aluminum spinel phase is present in the composition of this aspect in an amount of 20-60% by weight. In various embodiments described herein, the zinc-aluminum spinel phase is present in the composition in an amount in the range of 20-55% by weight, for example, 20-50% by weight, or 20-45% by weight, or 20-40% by weight, or 20-35% by weight. In various embodiments described herein, the zinc-aluminum spinel phase is present in the composition in an amount in the range of 25-60% by weight, for example, 25-55% by weight, or 25-50% by weight, or 25-45% by weight, or 25-40% by weight, or 25-35% by weight.
[0036] In various embodiments, the zinc-aluminum spinel phase of the composition described herein has an average grain size in the range of 1-100 nm. The average grain size of the zinc-aluminum spinel phase of the composition described herein can be varied. For example, in various embodiments the zinc-aluminum spinel phase has an average grain size of 1-75 nm, for example, or 1-50 nm. In various embodiments, the zinc-aluminum spinel phase has an average grain size of 2.5-100 nm, for example, or 2.5-75 nm, or 2.5-50 nm. In various embodiments, the zinc-aluminum spinel phase has an average grain size of 5-100 nm, for example, or 5-75 nm, or 5-50 nm. Like the grain size of the ZnO phase, the smaller grain size of the zinc-aluminum spinel phase corresponds to a higher surface area and provides a higher catalytic activity.
[0037] Since zinc-aluminum spinel itself generally has an idealized chemical formula of ZnAl2O4, it is desirable to select a ratio of zinc to aluminum that, along with the other elemental components, provides the desired amount of the spinel structure. In various embodiments of the compositions otherwise described herein, zinc is present in an amount in excess of that necessary to form the spinel structure, i.e., to provide a substantial amount of ZnO, as described herein.
[0038] As noted above, the Cu dopant is present in the composition according to this aspect of the disclosure in an amount in the range of 0.1-20 wt %. The amount of the Cu dopant in the composition described herein may also be varied. In various embodiments, the Cu dopant is present in the composition in an amount in the range of 0.1-15 wt %, for example, in the range of 0.1-10 wt %. In various embodiments, the Cu dopant is present in the composition in an amount in the range of 0.5-20 wt %, for example, in the range of 0.5-15 wt %, or in the range of 0.5-10 wt %. In various embodiments, the Cu dopant is present in the composition in an amount in the range of 1-20 wt %, for example, in the range of 1-15 wt %, or in the range of 1-10 wt %. The inventors of the present application have determined that only a small amount of copper is necessary for the desired activity and stability, and therefore in various embodiments, no more than 15 wt % of the Cu dopant is present in the material, for example, no more than 10 wt % of the Cu dopant.
[0039] In various embodiments, the catalyst composition of the disclosure has little to no crystalline Al2O3 phase. For example, in various embodiments, the amount of crystalline Al2O3 phase in the catalyst composition is no more than 5 wt%, for example, no more than 4 wt%, or no more than 3 wt%, or no more than 2 wt%, or no more than 1 wt%. In various embodiments, the catalyst composition comprises an amount of Al2O3 phase in the range of 1-6 wt%, or 1-4 wt%, or 1-3 wt%, or 1-2 wt%. In various embodiments, the catalyst composition does not contain any significant amount of crystalline Al2O3 phase, for example, no more than 0.5 wt%.
[0040] In an alternative definition of a useful catalyst composition of the disclosure, the catalyst composition is a calcined methanol reforming catalyst composition comprising oxides of Zn, Al and Cu, wherein:
[0041] Zn is present in the composition in a total amount of 40-80 wt % (e.g., 60-80 wt %), calculated as ZnO;
[0042] Al is present in the composition in a total amount of 20-50 wt % (e.g., 20-40 wt %), calculated as Al2O3; and
[0043] Cu is present in the composition in a total amount of 0.5-20 wt % (e.g., 1-15 wt %, or 1-10 wt %), calculated as CuO,
[0044] wherein the catalyst composition comprises at least 20 wt % (e.g., at least 30 wt %, or at least 40 wt %) zinc-aluminum spinel as determined by XRD and calculated as ZnAl2O4.
[0045] The catalyst composition according to this aspect of the disclosure may, in various embodiments, have the features as generally described above with respect to the previous aspects.
[0046] In various embodiments of the catalyst composition of the present disclosure, zinc is present in the composition described herein in addition in a total amount of 40-80% by weight, calculated as ZnO. The amount of zinc in the catalyst composition of the present disclosure may vary within this range. For example, in various embodiments described herein in addition, zinc is present in the composition in a total amount of 40-75% by weight, for example, 40-70% by weight, or 40-65% by weight, or 40-60% by weight, calculated as ZnO. In various embodiments described herein in addition, zinc is present in the composition in a total amount of 45-80% by weight, for example, 45-75% by weight, or 45-70% by weight, or 45-65% by weight, or 45-60% by weight, calculated as ZnO. In various embodiments described herein in addition, zinc is present in the composition in a total amount of 50-80% by weight, for example, 50-75% by weight, or 50-70% by weight, or 50-65% by weight, or 50-60% by weight, calculated as ZnO. In various embodiments described herein, zinc is present in the composition in a total amount of 55-80% by weight, e.g., 55-75% by weight, or 55-70% by weight, or 55-65% by weight, or 55-60% by weight, calculated as ZnO. In various embodiments described herein, zinc is present in the composition in a total amount of 60-80% by weight, e.g., 60-75% by weight, or 60-70% by weight, or 60-65% by weight, calculated as ZnO.
[0047] In various embodiments described herein, aluminum is present in the composition in a total amount of 20-50% by weight, calculated as Al2O3. The amount of aluminum in the catalyst composition of the present disclosure may vary within this range. For example, in various embodiments described herein, aluminum is present in the composition in a total amount of 20-45% by weight, for example, 20-40% by weight, or 20-35% by weight, or 20-30% by weight, calculated as Al2O3. In various embodiments described herein, aluminum is present in the composition in a total amount of 25-50% by weight, for example, 25-45% by weight, or 25-40% by weight, or 25-35% by weight, or 25-30% by weight, calculated as Al2O3. In various embodiments described herein, aluminum is present in the composition in a total amount of 30-50% by weight, for example, 30-45% by weight, or 30-40% by weight, or 30-35% by weight, calculated as Al2O3.
[0048] In various embodiments described herein in addition, copper is present in the composition in a total amount of 0.5-20% by weight, calculated as CuO. The amount of copper in the catalyst composition of the present disclosure may vary within this range. For example, in various embodiments described herein in addition, copper is present in the composition in a total amount of 0.5-15% by weight, for example, in a total amount of 0.5-10% by weight, or 0.5-5% by weight. In various embodiments described herein in addition, copper is present in the composition in a total amount of 1-20% by weight, for example, 1-15% by weight, or 1-10% by weight, or 1-5% by weight. In various embodiments described herein in addition, copper is present in the composition in a total amount of 2-20% by weight, for example, 2-15% by weight, or 2-10% by weight, or 2-5% by weight.
[0049] In various embodiments of the composition described in addition herein, the composition may further comprise one or more metal substances. For example, in various such embodiments, the composition comprises one or more of the following: sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium; these do not generally form part of the crystalline spinel. The metal may be provided (e.g., by impregnation) in the form of any compound that provides the metal to the catalyst composition in addition (e.g., in the form of an oxide) (e.g., before the calcination step). For example, in various embodiments, the metal is provided in the form of a salt selected from the following: carbonates, nitrates, acetates, formates, oxalates, molybdates and citrates. In various embodiments described in addition herein, potassium is provided in the form of a salt, for example, in the form of potassium acetate, introduced by impregnation before the calcination step. In various embodiments described in addition herein, magnesium is provided in the form of a salt, for example, in the form of magnesium acetate, introduced by impregnation before the calcination step. Typically, such a metal may be present in the catalyst composition in the form of an oxide, typically separated from the crystalline spinel structure.
[0050] In various embodiments of the compositions described herein, the compositions comprise only one additional metal substance selected from sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium. One of ordinary skill in the art will select one or more appropriate metal substances based on the description herein. For example, in various embodiments of the compositions described herein, the compositions comprise one or more (e.g., one) metal substances selected from sodium, potassium, magnesium and calcium. In another example, in various embodiments of the compositions described herein, the compositions comprise one or more (e.g., one) metal substances selected from potassium and magnesium. In various embodiments of the compositions described herein, the compositions comprise a first metal substance selected from sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium (e.g., selected from sodium, potassium, magnesium and calcium) and a second metal substance selected from sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium (e.g., selected from sodium, potassium, magnesium and calcium). For example, in various embodiments, the compositions comprise a first metal substance selected from sodium and potassium and a second metal substance selected from magnesium and calcium. In another example, in various embodiments of the compositions otherwise described herein, the composition includes potassium as the first metal species and magnesium as the second metal species.
[0051] Without intending to be bound by theory, it is believed that the metal species described herein can act as promoters to desirably modify reactivity.
[0052] The metal species can be provided in various amounts. For example, various embodiments of the catalyst composition described herein may include one or more metal species selected from sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium, present in a combined amount of 0.05-20% by weight. For example, in various embodiments described herein, the catalyst composition described herein may further include one or more of the following: sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium, present in a combined amount of 0.05-15% by weight, or 0.05-10% by weight, or 0.05-5% by weight, or 0.1-20% by weight, or 0.1-15% by weight, or 0.1-10% by weight, or 0.1-5% by weight, or 0.5-20% by weight, or 0.5-15% by weight, or 0.5-10% by weight, or 0.5-5% by weight. In various desired embodiments, the total amount of these metal species is no more than 10% by weight, for example, no more than 5% by weight.
[0053] In certain embodiments described herein, the catalyst composition further comprises at least one of magnesium and potassium. For example, in various embodiments described herein, the catalyst further comprises at least one of the following: magnesium, present in an amount of 0.1-2% by weight, calculated as MgO; and potassium, present in an amount of 0.25-3% by weight, calculated as K2O. In various embodiments described herein, the catalyst further comprises magnesium in an amount of 0.1-1.5% by weight, for example, 0.1-1.0% by weight, or 0.1-0.75% by weight, or 0.1-0.5% by weight, calculated as MgO. In various embodiments described herein, the catalyst further comprises magnesium in an amount of 0.25-2.0% by weight, for example, 0.25-1.5% by weight, or 0.25-0.75% by weight, or 0.25-0.5% by weight, calculated as MgO. In various embodiments described herein, the catalyst further comprises magnesium present in an amount of 0.5-2.0 wt %, for example, 0.5-1.5 wt %, or 0.5-1.0 wt %, or 0.5-0.75 wt %, calculated as MgO. In various embodiments described herein, the catalyst further comprises potassium present in an amount of 0.25-2.75 wt %, for example, 0.25-2.5 wt %, or 0.25-2.25 wt %, or 0.25-2 wt %, calculated as K2O. In various embodiments described herein, the catalyst further comprises potassium present in an amount of 0.5-3 wt %, for example, 0.5-2.75 wt %, or 0.5-2.5 wt %, or 0.5-2.25 wt %, or 0.5-2 wt %, calculated as K2O.
[0054] It is noteworthy that the inventors of the present application have determined that relatively small amounts of copper can be used while providing good catalyst activity and stability at high temperatures. In various embodiments described in addition herein, the catalyst composition does not include more than 20% by weight of copper, calculated as CuO. For example, in various embodiments described in addition herein, the catalyst composition does not include more than 15% by weight of copper, calculated as CuO. And in various embodiments, the catalyst composition does not include more than 10% by weight of copper, calculated as CuO. The inventors of the present application have found that by limiting the amount of copper in the methanol reforming catalyst, the catalyst can remain active at high temperatures without degradation. In addition, the inventors of the present application have found that even in the presence of a relatively small amount of copper, the catalyst exhibits high methanol conversion and hydrogen selectivity.
[0055] As described above, chromium is conventionally used to provide methanol shift catalysts having excellent activity, selectivity, and stability at elevated temperatures. However, chromium is toxic and carcinogenic, and it is therefore desirable to avoid its use where possible. The inventors of the present application have discovered that the catalysts of the present disclosure exhibit good activity and stability at high temperatures even in the absence of chromium. Therefore, in various embodiments described further herein, the catalyst composition does not contain more than 1 wt % chromium, calculated in the form of Cr2O3. For example, in various embodiments described further herein, the catalyst composition does not contain more than 0.5 wt %, or more than 0.1 wt %, or more than 0.01 wt % chromium, calculated in the form of Cr2O3.
[0056] The catalyst compositions described herein may consist essentially of oxides of copper, aluminum, and zinc. For example, in various embodiments of the catalyst compositions described herein, the total amount of oxides of Cu (calculated as CuO), Al (calculated as Al2O3), and Zn (calculated as ZnO) is at least 90% by weight of the catalyst composition, e.g., at least 95% by weight.
[0057] The inventors of the present application have also pointed out that it may be desirable to add certain metal species (e.g., as promoters). Thus, in various embodiments of the catalyst compositions otherwise described herein, the total amount of oxides of Cu (calculated as CuO), Al (calculated as Al2O3) and Zn (calculated as ZnO) and oxides of metal species selected from sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium (all calculated in the form of the most common oxides) is at least 95% by weight of the catalyst composition, e.g., at least 98% by weight.
[0058] In various embodiments described herein, the catalyst composition has 20-500 m 2 For example, in various embodiments described herein, the catalyst composition has a BET surface area in the range of 20 to 500 m 2 / g, for example, 20-400 m 2 / g, or 20-300 m 2 / g, or 20-200 m 2 / g, or 30-500 m 2 / g, or 30-400 m 2 / g, or 30-300m 2 / g, or 30-200 m 2 / g, or 40-500 m 2 / g, 40-400 m 2 / g, or 40-300 m 2 / g, or 40-200 m 2 / g, or 50-500 m 2 / g, or 50-400 m 2 / g, or 50-300 m 2 / g, or 50-200 m 2 One of ordinary skill in the art will use conventional techniques together with the synthetic techniques described herein to provide a material with a desired surface area.
[0059] In various embodiments described herein, the catalyst composition has a pore volume accessible to N2 of 0.05-1 cc / g. For example, in various embodiments described herein, the catalyst composition has a pore volume accessible to N2 of 0.05-1.0 cc / g, for example, 0.05-0.8 cc / g, or 0.05-0.6 cc / g, or 0.05-0.4 cc / g, or 0.05-0.35 cc / g, or 0.1-0.8 cc / g, or 0.1-0.6 cc / g, or 0.1-0.4 cc / g, or 0.1-0.35 cc / g, or 0.2-0.8 cc / g, or 0.2-0.6 cc / g, or 0.2-0.4 cc / g, or 0.2-0.25 cc / g. One of ordinary skill in the art will use conventional techniques together with the synthetic techniques described herein to provide a material having a desired pore volume.
[0060] The inventors of the present application have discovered that co-precipitation techniques can be used to prepare the copper, zinc and aluminum mixed oxide catalysts of the present disclosure. Other techniques such as impregnation can optionally be used to add additional materials, for example, those that are not easily co-precipitated. Another aspect of the present disclosure is a method for preparing a methanol reforming catalyst composition. The method includes providing an aqueous precursor solution comprising zinc ions, aluminum ions and copper ions; precipitating a solid catalyst precursor comprising zinc, aluminum and copper salts from the aqueous precursor solution, and then calcining the solid catalyst precursor to provide a catalyst composition.
[0061] As described above, the method includes providing a precursor solution comprising zinc ions, aluminum ions and copper ions. In various embodiments described herein, providing a precursor aqueous solution includes dissolving one or more salts containing zinc ions, aluminum ions and copper ions in water. For example, in various embodiments described herein, one or more salts can be selected from zinc nitrate, zinc sulfate, zinc carbonate, zinc acetate, zinc chloride, zinc bromide, zinc iodide, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum acetate, aluminum chloride, aluminum bromide, aluminum iodide, copper nitrate, copper sulfate, copper carbonate, copper acetate, copper chloride, copper iodide and copper bromide. In various embodiments of the present disclosure, one or more salts containing zinc ions, aluminum ions and copper ions have the same counter ions. In other embodiments described herein, one or more salts containing zinc ions, aluminum ions and copper ions have different counter ions. In a specific embodiment of the disclosure described herein, providing a precursor solution includes dissolving one or more of zinc nitrate, aluminum nitrate and copper nitrate in water.
[0062] As described above, the method includes precipitating a solid catalyst precursor from a solution. Precipitation can be achieved by making the pH of the solution reach a range of 5 to 7.5. For example, in various embodiments of the method described in addition herein, the pH of the precursor solution is reached, for example, 5-7.2, or 5-7, or 5-6.8, or 5-6.5, or 5-6.2, or 5-6, or 5.5-7.5, or 5.5-7.2, or 5.5-7, or 5.5-6.8, or 5.5-6.5, or 6-7.5, or 6-7.2, or 6-7, or 6.5-7.5, or 6.5-7.2. Such a pH range can be maintained desirably during the entire precipitation period.
[0063] In some embodiments of the methods described herein, the precipitation step comprises adding an alkaline solution comprising carbonate ions and hydroxide ions to the precursor aqueous solution. In some embodiments of the methods described herein, the alkaline solution comprises sodium carbonate (e.g., 15-35% by weight, or 20-30% by weight) and sodium hydroxide (e.g., 5-15% by weight). Of course, other alkaline solutions may be used, for example, potassium carbonate and / or potassium hydroxide may be used instead of their sodium analogs.
[0064] In various embodiments of the methods described herein, the temperature of the precursor solution is maintained at 30° C. to 100° C. throughout the precipitation. For example, in various embodiments of the methods described herein, the temperature of the precursor solution is maintained in the range of 30-100° C., for example, 30-90° C., or 30-80° C., or 40-100° C., or 40-90° C., or 40-80° C., or 50-100° C., or 50-90° C., or 50-80° C. throughout the precipitation.
[0065] Those of ordinary skill in the art may select the time course required for precipitation. In various embodiments of the method described in addition herein, precipitation is performed over a period of 0.5-2 hours, for example, over a period of 0.5-1.5 hours, or 0.5-1 hours, or 1-2 hours, or 1-1.5 hours, or 1.5-2 hours. For example, in a specific embodiment, precipitation takes 1 hour. However, other times may be used.
[0066] As described above, the method includes calcining the solid catalyst precursor. In some embodiments of the method described in addition herein, the method further includes separating and washing the solid catalyst precursor before calcining the solid catalyst precursor. Conventional methods can be used without specific restrictions. Separation can be carried out by any desired method (for example, filtering or centrifugation) for separating the solid precipitate from the liquid solution. Washing can be carried out by rinsing with deionized water.
[0067] In some embodiments of the methods described herein, the solid catalyst precursor is aged prior to calcination, e.g., after separation but prior to drying. In some embodiments of the methods described herein, the solid catalyst precursor is aged for a period of time in the range of 5 minutes to 1 hour, e.g., 5 minutes to 45 minutes, or 5 minutes to 30 minutes, or 5 minutes to 15 minutes, or 15 minutes to 1 hour, or 15 minutes to 45 minutes, or 15 minutes to 30 minutes, or 30 minutes to 1 hour, or 30 minutes to 45 minutes, or 45 minutes to 1 hour.
[0068] In some embodiments of the methods described herein, the solid catalyst precursor is dried before calcination. Here, too, conventional methods may be used without specific limitations. In some embodiments of the methods described herein, the solid catalyst precursor is dried at a temperature in the range of 40° C. to 200° C. for a period of time in the range of 15 minutes to 36 hours. However, one of ordinary skill in the art will appreciate that other conditions may be used (e.g., drying the material under ambient conditions), and that a separate drying step may not be necessary for some samples because water will be removed during the initial stages of heating for calcination.
[0069] The material is calcined via treatment with oxygen at high temperature (typically in air) so as to substantially convert the zinc, aluminum and copper salts of the precipitate into oxides. In various embodiments of the methods otherwise described herein, the temperature of calcination is in the range of 200-600°C. For example, in various embodiments of the methods otherwise described herein, the temperature of calcination is 300-700°C, for example, 300-650°C, or 300-600°C, or 300-550°C, or 300-500°C, or 350-700°C, or 350-650°C, or 350-600°C, or 350-550°C, or 400-700°C, or 400-650°C, or 400-600°C, or 450-700°C, or 450-650°C, or 500-700°C.
[0070] One of ordinary skill in the art will select a calcination time sufficient to substantially convert the precipitated salt into the oxide as described above. In some embodiments of the methods otherwise described herein, the solid catalyst precursor is calcined for a period of time in the range of 5 minutes to 24 hours. For example, in various embodiments of the methods otherwise described herein, the solid catalyst precursor is calcined for a period of time in the range of 5 minutes to 12 hours, or 5 minutes to 8 hours, or 1 hour to 24 hours, or 1-12 hours, or 1-8 hours, or 2-24 hours, or 2-12 hours, or 2-8 hours.
[0071] As noted above with respect to various aspects and embodiments of the catalyst compositions of the present disclosure, metal sources other than Zn, Al or Cu (e.g., Na, K, Mg, Ca, La, Ce, Ge, Ba or Zr sources) may be, for example, carbonates, nitrates, acetates, formates, oxalates, molybdates, or citrates, or any compound that provides alkali metals and / or alkaline earth metals to the calcined catalyst composition. Some of these substances may be precipitated with zinc, aluminum and copper salts. In other embodiments of the methods described herein, the methods further include providing one or more of the following to the composition via an impregnation step: sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium. In particular embodiments, the methods described herein include providing one or more of potassium and magnesium to the composition via an impregnation step. In various embodiments of the methods described herein, the methods include impregnating the calcined composition via an incipient wetness impregnation method. For example, in various embodiments of the methods described herein, the methods include impregnating the calcined composition with an aqueous solution of potassium acetate, and calcining the impregnated composition. For example, in various embodiments of the methods described herein, the methods include impregnating the calcined composition with an aqueous solution of magnesium acetate, and calcining the impregnated composition. For example, in various embodiments of the methods described herein, the methods include impregnating the calcined composition with an aqueous solution of potassium acetate and magnesium acetate, and calcining the impregnated composition.
[0072] In various embodiments of the methods described herein, the calcining step occurs before the impregnation step. In various embodiments of the methods described herein, the calcining step occurs after the impregnation step. In various embodiments of the methods described herein, the calcining step occurs both before and after the impregnation step. Post-impregnation drying and calcining can be carried out, for example, at the temperature and time ranges disclosed above for calcination of the precipitate.
[0073] Another aspect of the present disclosure provides a catalyst composition (eg, a methanol reforming catalyst composition) prepared by the method otherwise described herein.
[0074] Advantageously, the inventors of the present application have determined that the catalyst compositions disclosed herein can catalyze high temperature methanol reforming reactions with efficiencies comparable to conventional chromium-containing and copper-containing catalyst materials, and in various embodiments can operate over a wider range of water-methanol ratios and over a wider range of high temperatures than conventional catalyst materials. In addition, the inventors of the present application have determined that the use of such catalyst compositions can catalyze high temperature methanol reforming reactions with high efficiencies comparable to conventional high copper-containing catalyst materials.
[0075] Compositions described herein are particularly useful in, for example, methanol reforming reactions carried out at relatively high temperatures. As understood by those of ordinary skill in the art, methanol reforming reactions are generally provided with hydrogen by methanol, for example, by converting water and methanol into hydrogen and carbon oxides (mostly carbon dioxide, desirably). Therefore, another aspect of the present disclosure is a method for carrying out a methanol reforming reaction, which includes contacting a feed comprising water and methanol with a catalyst composition described herein under certain conditions to cause the formation of hydrogen and carbon dioxide. For example, the feed can be formed by the gasification of an organic raw material such as coal or biomass.
[0076]
[0013] Thus, one embodiment of the present disclosure provides a method of conducting a methanol reforming reaction comprising contacting a feed comprising water and methanol with a catalyst composition otherwise described herein at a temperature of at least 300°C.
[0077] The feed preferably has a large amount of methanol. For example, in various embodiments described herein, the feed comprises at least 10 mol % methanol, for example, at least 20 mol % methanol. This can provide a large amount of hydrogen for use in, for example, a fuel cell. However, in other embodiments, a feed leaner in methanol can be used, for example, to remove a small amount of methanol from a feed stream to be used for other purposes.
[0078] As described above, the method includes contacting a feed comprising water and methanol with a methanol reforming catalyst composition. In various embodiments of the method described further herein, the molar ratio of water to methanol present in the feed is up to 2.5. For example, in certain such embodiments, the molar ratio of water to methanol in the feed is up to 2.4, or up to 2.3, or up to 2.2, or up to 2.1, or up to 2.0. The inventors of the present application have pointed out that the H2 yield will deteriorate at a higher ratio of water to methanol. And in various embodiments of the method described further herein, the molar ratio of water to methanol present in the feed stream is at least 0.5, for example, at least 0.6, or at least 0.8, or at least 1. The inventors of the present application have pointed out that coke formation and associated pressure reduction in the catalyst bed at a lower steam: methanol ratio will be problematic. Thus, in various embodiments of the processes described herein, the feed has a steam:methanol ratio in the range of 0.5-2.5, e.g., 0.5-2.3, or 0.5-2, or 0.5-1.8, or 0.5-1.5, or 0.7-2.5, or 0.7-2.3, or 0.7-2, or 0.7-1.8, or 0.7-1.5, or 1-2.5, or 1-2.3, or 1-2, or 1-1.8, or 1-1.5.
[0079] As described above, the process includes contacting the feed at a temperature of at least 300°C. The inventors of the present application have discovered that the catalysts described herein may be particularly useful in such high temperature methanol conversion processes. In various embodiments of the process otherwise described herein, at 300-550°C, or 325-550°C, or 350-550°C, or 375-550°C, or 400-550°C, or 425-550°C, or 450-550°C, or 300-525°C, or 325-525°C, or 350-525°C, or 375-525°C, or 400-525°C, or 425-525°C, or 300-500°C The feed is contacted with the catalyst composition at a temperature of 325-500°C, or 350-500°C, or 375-500°C, or 400-500°C, or 300-475°C, or 325-475°C, or 350-475°C, or 375-475°C, or 300-450°C, or 325-450°C, or 350-450°C, or 300-425°C, or 325-425°C, or 300-400°C.
[0080] The contact of the feed with the catalyst composition described herein can be carried out in various ways well known to those of ordinary skill in the art. Conventional equipment and methods can be used in combination with the catalyst composition of the present disclosure to provide beneficial performance. Therefore, the catalyst can be contained in a bed in a reactor vessel or distributed between multiple beds in a reactor. The reaction system can contain one or more reaction vessels in series. The feed to the reaction zone can flow vertically upward in a typical plug flow reactor, or flow downward through the catalyst bed, or flow horizontally through the catalyst bed in a radial flow reactor.
[0081] The gas hourly space velocity will depend on various factors, which will be clear to one of ordinary skill in the art. In various embodiments of the methods described herein, the gas hourly space velocity is 200-30000 h -1 The feed is contacted with the catalyst composition at a gas hourly space velocity (GHSV) of 1000 to 30000 h. -1 , or 5000-30000 h -1 or 10000-30000 h -1 , or 200 h -1 -20000 h -1 , or 1000-20000 h -1 , or 5000-20000 h -1 , or 10000-20000 h -1 The feed is contacted with a given catalyst composition at a gas hourly space velocity within a range of .
[0082] In various embodiments of the processes otherwise described herein, the feed is contacted with the catalyst composition at a pressure of ambient to 600 psi, e.g., ambient to 550 psi, or ambient to 500 psi, or ambient to 450 psi, or ambient to 400 psi, or ambient to 350 psi. For example, in various embodiments, the feed contacted with the catalyst composition is at a pressure of 50 psi to 600 psi, or 50 psi to 550 psi, or 50 psi to 500 psi, or 50 psi to 450 psi, or 50 psi to 400 psi, or 50 psi to 350 psi, or 100 psi to 600 psi, or 100 psi to 550 psi, or 100 psi to 500 psi, or 100 psi to 450 psi, or 100 psi to 400 psi, or 100 psi to 35 psi, or 150 psi to 600 psi, or 150 psi to 550 psi, or 150 psi to 500 psi, or 150 psi to 450 psi, or 150 psi to 400 psi, or 150 psi to 350 psi, or 200 psi to 600 psi, or 200 psi to 550 psi, or 200 psi to 500 psi, or 200 psi to 450 psi, or 200 psi to 400 psi, or 200 psi to 350 psi, or 250 psi to 600 psi, or 250 psi to 550 psi, or 250 psi to 500 psi, or 250 psi to 450 psi, or 250 psi to 400 psi, or 250 psi to 350 psi.
[0083] Of course, one of ordinary skill in the art will typically select reaction conditions, for example, to balance H2 yield, catalyst performance, thermal durability, and coke formation. For example, a high steam: methanol ratio can result in a lower hydrogen yield and can therefore result in poor performance in a hydrogen fuel cell, while a low steam: methanol ratio can result in coke formation and therefore a significant pressure reduction in the catalyst bed. Similarly, if the operating pressure is below ambient pressure, the hydrogen yield will be reduced; but high pressures have higher power requirements, thereby reducing cost effectiveness. As is well known, temperature plays an important role in catalysis: too low will provide an undesirably low conversion rate, while overheating will damage the catalyst over time. Based on the teachings of the present disclosure, one of ordinary skill in the art can balance these considerations to provide an effective industrial process.
[0084] Desirably, the product containing hydrogen in contact with the catalyst can be directed to a fuel cell. The hydrogen-containing product is mostly composed of H2, CO and CO2. In certain embodiments of the present disclosure, H2 is present in the hydrogen-containing product in an amount in the range of 60-90% (by volume), for example, 65-90%, or 65-85%, or 65-80%, or 70-90%, or 70-85%, or 70-80%, or 75-90%, or 75-85%, or 75-80% (by volume). In certain embodiments of the present disclosure, CO is present in the hydrogen-containing product in an amount in the range of 1-20% (by volume), for example, 1-15%, or 1-10%, or 1-5%, or 5-20%, or 5-15%, or 5-10% (by volume). In certain embodiments of the present disclosure, CO2 is present in the hydrogen-containing product in an amount in the range of 10-40% (by volume), for example, in the range of 15-35%, or 15-30%, or 15-25%, or 20-40%, or 20-35%, or 20-30%, or 25-40%, or 25-35%, or 25-30% (by volume). Example
[0085] The following examples are illustrative of specific embodiments of the methods of the present disclosure and their various uses. They are presented for illustrative purposes only and are not to be considered as limiting the scope of the present disclosure. Example 1. Catalyst preparation
[0086] A mixed metal solution was prepared by dissolving 0.723 mol Zn(NO3)2 solution, 0.478 mol Al(NO3)3 and 0.048 mol Cu(NO3)2 solution in 500 mL of deionized water and by maintaining the temperature of the resulting aqueous solution at 50°C. An alkaline solution was prepared by mixing 240 mL of 10% NaOH solution and 960 mL of 25% Na2CO3 solution and by maintaining the temperature of the resulting aqueous solution at 50°C. At 60°C, mixing the metal solution and the alkaline solution at a constant pH of 6.8 produced the desired precipitate, which took 1 h. The resulting precipitate took 30 min to complete aging. The precipitate was then filtered and washed with deionized water and then dried at 120°C. The resulting dried material was calcined at 450°C for 2 hours to provide Catalyst E1.
[0087] A mixed metal solution was prepared by dissolving 0.723 mol Zn(NO3)2 solution, 0.478 mol Al(NO3)3 and 0.109 mol Cu(NO3)2 solution in 500 mL of deionized water and by maintaining the temperature of the resulting aqueous solution at 50°C. An alkaline solution was prepared by mixing 240 mL of 10% NaOH solution and 960 mL of 25% Na2CO3 solution and by maintaining the temperature of the resulting aqueous solution at 50°C. At 60°C, mixing the metal solution and the alkaline solution at a constant pH of 6.8 produced the desired precipitate, which took 1 h. The resulting precipitate took 30 min to complete aging. The precipitate was then filtered and washed with deionized water and then dried at 120°C. The resulting dried material was calcined at 450°C for 2 hours to provide Catalyst E2.
[0088] A mixed metal solution was prepared by dissolving 0.723 mol Zn(NO3)2 solution, 0.478 mol Al(NO3)3 and 0.048 mol Cu(NO3)2 solution in 500 mL of deionized water and by maintaining the temperature of the resulting aqueous solution at 50°C. An alkaline solution was prepared by mixing 240 mL of 10% NaOH solution and 960 mL of 25% Na2CO3 solution and by maintaining the temperature of the resulting aqueous solution at 50°C. Mixing the metal solution and the alkaline solution at a constant pH of 6.8 at 60°C produced the desired precipitate, which took 1 h. The resulting precipitate took 30 min to complete aging. The precipitate was then filtered and washed with deionized water and then dried at 120°C. The resulting dried material was calcined at 450°C for 2 hours. K and Mg as promoters were added by adding a mixed aqueous solution of magnesium acetate and potassium acetate by incipient wetness impregnation. The material was then dried at 120°C and calcined at 450°C for 2 hours to provide Catalyst E3.
[0089] A mixed metal solution was prepared by dissolving 0.723 mol Zn(NO3)2 solution and 0.478 mol Al(NO3)3 solution in 500 mL deionized water and by maintaining the temperature of the resulting aqueous solution at 50°C. An alkaline solution was prepared by mixing 240 mL of 10% NaOH solution and 960 mL of 25% Na2CO3 solution and by maintaining the temperature of the resulting aqueous solution at 50°C. At 60°C, mixing the metal solution and the alkaline solution at a constant pH of 6.8 produced the desired precipitate, which took 1 h. The resulting precipitate took 30 min to complete aging. The precipitate was then filtered and washed with deionized water and then dried at 120°C. The resulting dried material was calcined at 450°C for 2 hours to provide comparative catalyst C1.
[0090] A mixed metal solution was prepared by dissolving 0.723 mol Zn(NO3)2 solution, 0.478 mol Al(NO3)3, 0.048 mol Cu(NO3)2 and 0.017 mol Mg(NO3)2 solution in 500 mL of deionized water and by maintaining the temperature of the resulting aqueous solution at 50°C. An alkaline solution was prepared by mixing 240 mL of 10% NaOH solution and 960 mL of 25% Na2CO3 solution and by maintaining the temperature of the resulting aqueous solution at 50°C. At 60°C, mixing the metal solution and the alkaline solution at a constant pH of 9 produced the desired precipitate, which took 1 h. The resulting precipitate took 30 min to complete aging. The precipitate was then filtered and washed with deionized water and then dried at 120°C. The resulting dried material was calcined at 450°C for 2 hours. The material was then dried at 120°C and calcined at 450°C for 2 hours to provide comparative catalyst C2.
[0091] A mixed powder was prepared by mixing 80.0 g Al2O3, 100 g ZrCO3 and 38 g deionized water for 10 min and then dried at 110°C for 3 h. The powder was then mixed with 4% graphite to prepare pellets and subsequently calcined at 350°C to 550°C for 6 h. A 14% Ni impregnation solution was prepared by dissolving Ni(NO3)2•6H2O nitrate in deionized water. The pellets were impregnated in the Ni solution for 0.5 h and then dried in a furnace at 110°C for 2 h and calcined at 300°C for 2 h and at 500°C for 4 h (ramp rate of 5°C / min). The Ni impregnation process was repeated 3-4 times until the desired Ni concentration (25 wt% Ni loaded on the ZrO2 and Al2O3 oxide mixture) was reached. The resulting material provided comparative catalyst C3.
[0092] Commercially available reference samples were also analyzed by XRD to determine their composition and used as further comparative catalysts (C4-C7).
[0093] Table 1. Catalyst composition
[0094] Example 2. Methanol conversion and hydrogen selectivity
[0095] The sample prepared in Example 1 was pelletized and loaded into a tubular reactor (inner diameter = 19 mm) at 7.25 mL for methanol steam reforming at high temperature. -1A reaction gas containing steam vapor and methanol (S / M, mol:mol) having a molar ratio of 1:1 was provided at a GHSV of 1.5 mol / mol. The GHSV was calculated based on the flow rate of the methanol / H2O feed at 1 atm and 25°C. The gas contacted the catalyst bed at 250 psi and >300°C to form a hydrogen-containing gas. Two reaction temperatures, 400°C and 450°C, were tested at a reaction pressure of 250 psi. All tests were completed within 72 hours. The methanol conversion was calculated from the difference between the inlet and outlet of methanol. The methanol conversion results are shown in Table 2 together with the hydrogen selectivity.
[0096] Table 2. Methanol conversion and hydrogen selectivity
[0097] ZnO and ZnAl2O4 spinel based catalysts with Cu as promoter (E1 and E2) outperformed their Cu-free counterparts (C1). E1 and E2 were quite similar in activity and selectivity at 450°C, indicating that the addition of an additional 5.5% Cu did not result in significant differences under high temperature reaction conditions. However, the higher Cu content in E2 resulted in slightly better activity than E1 at lower temperatures (e.g., 400°C). The methanol conversion of E3 was slightly higher with the addition of 0.8% MgO and 1.2% K2O promoters. Although C2, like E3, had the same active composition, it was precipitated in an alkaline environment at pH=9. The resulting catalyst exhibited much lower activity compared to its counterpart E3, with methanol conversion reduced by 32% and 26% at 400°C and 450°C, respectively. Ni-based catalyst C3 was also prepared and tested for methanol steam reforming. Although its activity is good under the same test conditions, the selectivity of C3 to H2 is unacceptable, 35% compared to ~75% for ZnO and ZnAl2O4 spinel based catalysts. Reference C4 is a Zn / Cr catalyst, which has been commonly used for high temperature methanol steam reforming. Both its activity and H2 selectivity are very close to the Cu promoted ZnO-ZnAl2O4 catalyst. Reference samples of C6 and C7 are both CuO / ZnO / Al2O3 catalysts with high CuO loading. Although they show significant activity at 400°C and 450°C under the test conditions, they deactivate very quickly during the extended test due to Cu sintering.
[0098] Example 3. Effect of reaction temperature and steam / methanol (S / M) ratio
[0099] The catalysts were also investigated for reaction temperature and steam / methanol (S / M) ratio. The reaction temperature ranged from 330°C to 500°C and the reaction pressure was 250 psi. In the tests, the catalysts were tested at 300°C for 3650 h.-1 The reaction gas containing water vapor and methanol was provided at a GHSV of 1.3 GHz. All tests were completed within 72 hours. The details of the tests are described in Table 3.
[0100] Table 3. Relationship between methanol conversion rate, reaction temperature and S / M ratio
[0101] Compared to the chromium-containing reference sample C4, at 330°C, the ZnO-ZnAl2O4 catalyst of E1 shows a much higher MeOH conversion. For example, at S / M=1, the conversion is 83% vs. 51%. At higher temperatures such as 400°C and 450°C, the difference in conversion between the two catalysts is very insignificant. Indeed, at all tested temperatures, E1 shows a much more consistent methanol conversion. MeOH conversion is generally positively correlated with the S / M ratio. This is also true for E1. However, C4 shows a higher MeOH conversion at an S / M of 0.6 than at ratios of 1 and 2. Therefore, E1 is superior to the chromium-containing catalyst C4 because it provides a more stable and consistent methanol conversion at all tested S / Ms and temperatures.
[0102] Example 4. Methanol conversion over time
[0103] The methanol steam reforming rate of catalyst E1 was tested over time and the results are shown in Figure 1 At 330°C, 250 psi and 3650h -1 The reaction was run continuously at a GHSV of 1.30 for 175 h. Figure 1 The methanol conversion, hydrogen selectivity, carbon monoxide selectivity, and carbon dioxide selectivity showed negligible deactivation during 175 h of continuous operation, indicating the long-term stability of catalyst E1.
[0104] Catalyst E1 showed excellent activity, stability and constant H2 selectivity. Without being bound by theory, its high activity is due to two reasons. One is the addition of Zn 2+ The oxygen vacancies generated by the incorporation into the ZnAl2O4 lattice and another reason is due to the free and highly active ZnO phase. ZnO tends to show higher methanol steam reforming activity than ZnAl2O4, and the spinel structure of ZnAl2O4 is known to be thermally stable. Figure 1 The long-term stability and high methanol conversion of catalyst E1 shown in Figure 1 are attributed to the presence of both ZnO and ZnAl2O4 in the catalyst. In terms of product selectivity, 73-74% H2, 1-3% CO and 23-25% CO2 were present in the dry effluent gas, and no CH4 was detected. In addition, as Figure 2As shown by the XRD data and Littlefield analysis shown in Figure 2, the spent E1 sample contained a higher percentage of ZnAl2O4, 46.5% compared to 42.9% for the fresh sample. Without being bound by theory, it is assumed that the phase transition from ZnO to ZnAl2O4 during the reaction enables the catalyst to maintain its high activity at a stable level. The spent catalyst was from 3650 h -1 160 hours of GHSV operation (24 hours at 400°C and 136 hours at 450°C).
[0105] Example 5. Effect of reaction pressure and space velocity
[0106] The effects of various reaction pressures and space velocities on methanol conversion and H2 selectivity were also studied, and the results are shown in Table 4. -1 By varying the pressure from 30 psi to 250 psi at 20000 h and S / M ratio of 1, C5 and C6 showed that the pressure had little effect on the catalytic activity. -1 At higher space velocities, the methanol conversion of the two catalysts dropped sharply. -1 The MeOH conversion rate was 68% at 20000 h. -1 , and C6 showed 26% MeOH conversion at 400°C and 450°C for 3650 h. -1 , and 1 S / M, the changes in MeOH conversion and H2 selectivity were negligible, and the results are shown in Table 5. Further, it was found that the activity was consistent, and no deactivation was found in the 72-hour test under the conditions listed in Table 5. The results of Tables 4 and 5 demonstrate that the ZnO-ZnAl2O4 catalyst with significantly less CuO can maintain activity at high temperatures without degradation. In addition, the ZnO-ZnAl2O4 catalyst with significantly less CuO (E1, Table 5) shows higher methanol conversion and hydrogen selectivity compared to the catalysts with more CuO (C1 and C2, Table 4).
[0107] Table 4. Relationship between methanol conversion and hydrogen selectivity and reaction conditions
[0108] *20000 h -1 The methanol conversion of C6 is the average over a 24-hour run. Within 24 hours, the activity at 400°C and 450°C decreased by 8% and 18%, respectively.
[0109] Table 5. Relationship between methanol conversion and hydrogen selectivity of ZnO-ZnAl2O4 catalyst and reaction conditions
[0110] Additional aspects of the disclosure are provided by the following enumerated embodiments, which may be combined in any number and in any combination that is not logically or technically inconsistent.
[0111] Embodiment 1. A methanol reforming catalyst composition comprising:
[0112] A ZnO phase, present in the composition in an amount of 20-75 wt %;
[0113] a zinc-aluminum spinel phase, present in the composition in an amount of 20-60% by weight; and
[0114] The Cu dopant phase is present in the composition in an amount of 0.1-20 wt %.
[0115] Embodiment 2. The catalyst composition of Embodiment 1, wherein the ZnO phase is present in an amount in the range of 30-70 wt%, or 40-60 wt%, or 30-50 wt%.
[0116] Embodiment 3. The catalyst composition of any of Embodiments 1-2, wherein the ZnO phase has an average crystallite size in the range of 1-50 nm (eg, 2.5-40 nm, or 5-30 nm).
[0117] Embodiment 4. The catalyst composition of any of Embodiments 1-3, wherein the zinc-aluminum spinel phase is present in the composition in an amount ranging from 30-60 wt%, or 40-60 wt%, or 30-50 wt%.
[0118] Embodiment 5. The catalyst composition of any of Embodiments 1-4, wherein the zinc-aluminum spinel phase has an average crystallite size in the range of 1-100 nm (eg, 2.5-75 nm, or 5-50 nm).
[0119] Embodiment 6. The catalyst composition of any one of Embodiments 1-5, wherein the Cu dopant is present in the composition in an amount of 0.5-15 wt % (eg, 1-10 wt %), calculated as CuO.
[0120] Embodiment 7. The catalyst composition of any of Embodiments 1-6, further comprising an Al2O3 phase in an amount of up to 5 wt%, eg, up to 4 wt%, or up to 3 wt%, up to 2 wt%, or up to 1 wt%.
[0121] Embodiment 8. The catalyst composition of any one of Embodiments 1-7, wherein Zn is present in the composition in a total amount of 40-80 wt % (eg, 50-80 wt %, or 60-80 wt %), calculated as ZnO.
[0122] Embodiment 9. The catalyst composition of any one of Embodiments 1-8, wherein Al is present in the composition in a total amount of 20-50 wt % (eg, 20-40 wt %), calculated as Al 2 O 3 .
[0123] Embodiment 10. The catalyst composition of any of Embodiments 1-9, wherein Cu is present in the composition in a total amount of 0.5-20 wt % (eg, 1-15 wt % or 1-10 wt %), calculated as CuO.
[0124] Embodiment 11. A calcined methanol reforming catalyst composition comprising oxides of Zn, Al and Cu, wherein:
[0125] Zn is present in the composition in a total amount of 40-80 wt % (e.g., 60-80 wt %), calculated as ZnO;
[0126] Al is present in the composition in a total amount of 20-50 wt % (e.g., 20-40 wt %), calculated as Al2O3; and
[0127] Cu is present in the composition in a total amount of 0.5-25 wt % (e.g., 1-15 wt %), calculated as CuO,
[0128] wherein the catalyst composition comprises at least 20 wt % (e.g., at least 30 wt %, or at least 40 wt %) zinc-aluminum spinel as determined by XRD and calculated as ZnAl2O4.
[0129] Embodiment 12. The calcined methanol reforming catalyst composition of Embodiment 11, as further described with the limitations explicitly set forth in any one of Embodiments 1-10.
[0130] Embodiment 13. The catalyst composition of any of Embodiments 1-12, further comprising one or more of Na, K, Mg, Ca, La, Ce, Ga, Ba, and Zr, present in a combined amount of 0.05-20 wt % (e.g., 0.1-10 wt %, or 0.5-5 wt %).
[0131] Embodiment 14. The catalyst composition of any one of Embodiments 1-13, further comprising at least one of the following:
[0132] Mg, present in an amount of 0.1-2 wt % (e.g., 0.5-1.5 wt %), calculated as MgO; and
[0133] K is present in an amount of 0.25-3 wt % (eg, 0.5-2 wt %), calculated as K2O.
[0134] Embodiment 15. The catalyst composition of any of Embodiments 1-14, wherein the catalyst composition does not comprise more than 15 wt % (eg, more than 10 wt %) copper, calculated as CuO.
[0135] Embodiment 16. The catalyst composition of any of Embodiments 1-15, wherein the catalyst composition does not contain more than 1 wt % (eg, more than 0.5, or more than 0.1 wt %, or more than 0.01 wt %) chromium, calculated as Cr2O3.
[0136] Embodiment 17. The catalyst composition of any of Embodiments 1-16, wherein the total amount of oxides of Cu (calculated as CuO), Al (calculated as Al2O3) and Zn (calculated as ZnO) is at least 90% by weight of the catalyst composition, e.g., at least 95% by weight.
[0137] Embodiment 18. The catalyst composition of any of Embodiments 1-17, wherein the total amount of oxides of Cu (calculated as CuO), Al (calculated as Al2O3) and Zn (calculated as ZnO) and oxides of metal species selected from sodium, potassium, magnesium, calcium, lanthanum, cesium, gallium, barium and zirconium is at least 95% by weight of the catalyst composition, for example, at least 98% by weight.
[0138] Embodiment 19. The catalyst composition of any one of Embodiments 1-18, having 20-500 m 2 / g (e.g., 30-400 m 2 / g, or 50-200 m 2 / g) of BET surface area.
[0139] Embodiment 20. The catalyst composition of any of Embodiments 1-19, having a N2-accessible pore volume of 0.05-1 cc / g (eg, 0.1-0.6 cc / g, or 0.2-0.35 cc / g).
[0140] Embodiment 21. A method for preparing a methanol reforming catalyst composition according to any one of Embodiments 1-20, the method comprising:
[0141] providing a precursor aqueous solution comprising zinc ions, aluminum ions and copper ions;
[0142] precipitating a solid catalyst precursor comprising zinc, aluminum and copper salts from the aqueous precursor solution; and then
[0143] The solid catalyst precursor is calcined to provide a catalyst composition.
[0144] Embodiment 22. The method of Embodiment 21, wherein providing the precursor solution comprises dissolving one or more of Zn(NO3)2, Al(NO3)3, and Cu(NO3)2 in water.
[0145] Embodiment 23. The method of Embodiment 21 or Embodiment 22, wherein precipitating the solid catalyst precursor comprises bringing the pH of the solution to a range of 5-7.5 (eg, 6.5-7.2).
[0146] Embodiment 24. The method of any one of Embodiments 21-23, wherein precipitating the solid catalyst precursor comprises adding an alkaline solution comprising carbonate ions and hydroxide ions to the precursor solution.
[0147] Embodiment 25. The method of any one of Embodiments 21-24, wherein the temperature of the precursor solution is maintained at 30°C to 100°C (eg, 50°C to 80°C) throughout the precipitation period.
[0148] Embodiment 26. The method of any one of Embodiments 21-25, further comprising aging, washing, and then drying the solid catalyst precursor prior to calcining the solid catalyst precursor.
[0149] Embodiment 27. The method of any one of Embodiments 21-26, wherein the temperature of calcining is 300-700°C (eg, 400-600°C).
[0150] Embodiment 28. The method of any of Embodiments 21-27, further comprising providing one or more of the following to the composition through an impregnation step: Na, K, Mg, Ca, La, Ce, Ga, Ba and Zr, wherein the impregnation step is followed by calcination.
[0151] Embodiment 29. The method of any one of Embodiments 21-27, further comprising providing one or more of K and Mg to the composition via an impregnation step, wherein the impregnation step is followed by calcination.
[0152] Embodiment 30. A catalyst composition prepared by the method of any one of Embodiments 21-29.
[0153] Embodiment 31. A method of conducting a methanol reforming reaction comprising contacting a feed comprising water and methanol with the catalyst composition of any of Embodiments 1-20 or 30 at a temperature of at least 300°C to form hydrogen and carbon dioxide.
[0154] Embodiment 32. The process of Embodiment 31, wherein the feed comprises at least 10 vol% methanol, eg, at least 20 vol% methanol.
[0155] Embodiment 33. The method of any of Embodiments 31-32, wherein the molar ratio of water to methanol present in the feed is at least 0.5 (eg, at least 0.6).
[0156] Embodiment 34. The method of any of Embodiments 31-33, wherein the molar ratio of water to methanol present in the feed is no greater than 2.5 (eg, no greater than 2).
[0157] Embodiment 35. The method of any one of Embodiments 31-32, wherein the molar ratio of water to methanol present in the feed is in the range of 0.5-2.5, for example, 0.5-2.3, or 0.5-2, or 0.5-1.8, or 0.5-1.5, or 0.7-2.5, or 0.7-2.3, or 0.7-2, or 0.7-1.8, or 0.7-1.5, or 1-2.5, or 1-2.3, or 1-2, or 1-1.8, or 1-1.5.
[0158] Embodiment 36. The method of any of Embodiments 31-35, wherein the feed is contacted with the catalyst composition at a temperature of 300-550°C (eg, 325-500°C).
[0159] Embodiment 37. The method of any one of Embodiments 31-36, wherein at 200-30000 h -1 The feed is contacted with the catalyst composition at a gas hourly space velocity of 1000 s.
[0160] Embodiment 38. The method of any of Embodiments 31-37, wherein the feed is contacted with the catalyst composition at a pressure of ambient to 600 psi (eg, ambient to 350 psi).
[0161] Embodiment 39. The method of any one of Embodiments 31-38, further comprising directing the contacted hydrogen-containing product to a fuel cell.
[0162] The details shown herein are presented as examples only and for the purpose of illustrative discussion of preferred embodiments of the invention, and are presented for the purpose of providing what is believed to be the most useful and easy-to-understand description of aspects of the principles and concepts of various embodiments of the invention. In this regard, no attempt is made to show the structural details of the invention in more detail than is necessary for a basic understanding of the invention, and the description in conjunction with the accompanying drawings and / or examples makes it clear to those skilled in the art how several forms of the invention are embodied in practice. Therefore, before describing the disclosed methods and apparatus, it should be understood that the aspects described herein are not limited to specific embodiments, instruments or configurations, and therefore can certainly be changed. It should also be understood that the terms used herein are only for the purpose of describing specific aspects, and are not intended to be limiting unless expressly defined herein.
[0163] The terms "a", "an", "the" and similar references used in the context of describing the present invention (especially in the context of the claims below) should be construed to cover both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. Recitation of ranges of values herein is merely intended to serve as a shorthand method of referring individually to each individual value falling within the range. Unless otherwise indicated herein, each individual value is incorporated into the specification as if it were individually recited herein. It will be further understood that the endpoints of each range are significant not only in relation to the other endpoints, but also independently of the other endpoints.
[0164] All methods described herein can be performed in the order of any suitable steps, unless otherwise indicated herein or clearly contradictory to the context. The use of any and all embodiments provided herein, or exemplary language (e.g., "such as") is intended only to better illustrate the present invention and does not set limitations on the scope of the present invention otherwise claimed. No language in the specification should be interpreted as indicating any unclaimed elements essential to the practice of the present invention.
[0165] Throughout the specification and claims, the words 'comprise,' 'comprising,' and the like are to be interpreted in an inclusive sense, as opposed to an exclusive or exhaustive sense; that is, in the sense of "including, but not limited to," unless the context clearly requires otherwise. Words using the singular or plural number also include the plural and singular, respectively. Additionally, when the words "herein," "above," and "below," and words of similar meaning, are used in this application, they shall refer to this application as a whole and not to any particular portion of this application.
[0166] As will be understood by one of ordinary skill in the art, each embodiment disclosed herein may comprise, consist essentially of, or consist of the specifically identified elements, steps, ingredients, or components thereof. As used herein, the transitional terms "comprise" or "comprises" are meant to include, but are not limited to, and permit the inclusion of unspecified elements, steps, ingredients, or components, even in large quantities. The transitional phrase "consisting of" excludes any unspecified elements, steps, ingredients, or components. The transitional phrase "consisting essentially of" limits the scope of the embodiment to the identified elements, steps, ingredients, or components and those that do not materially affect the embodiment.
[0167] Unless indicated to the contrary, the numerical parameters set forth in the specification and attached claims are approximations that may vary depending upon the desired properties sought to be obtained by the present invention. At the very least, and not as an attempt to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0168] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors resulting from the standard deviation found in their respective testing measurements.
[0169] The grouping of the optional elements or embodiments of the invention disclosed herein should not be construed as limiting. Each group member may be referred to and claimed individually or in any combination with other members of the group or other elements present herein. It is expected that one or more members of the group may be included in the group, or deleted from the group, due to convenience and / or patentable reasons. When any such inclusion or deletion occurs, it is considered that the specification contains the modified group, and therefore satisfies the written description of all Markush groups used in the appended claims.
[0170] Some embodiments of the present invention are described herein, including the best mode known to the inventor for carrying out the present invention. Of course, for those skilled in the art, when reading the foregoing description, variations of the embodiments described will become clear. The inventor expects that a skilled person will adopt such variations as appropriate, and the inventor intends to practice the present invention in a manner other than the specific description herein. Therefore, the present invention includes all modifications and equivalents of the subject matter recorded in the appended claims as allowed by applicable law. In addition, the present invention includes any combination of the elements described above in all possible variants thereof, unless otherwise indicated herein or clearly contradictory to the context.
[0171] Throughout this specification, a number of patents and printed publications are cited. Each of the cited references and printed publications is incorporated herein by reference in its entirety.
[0172] In addition, it should be understood that the embodiments of the invention disclosed herein are illustrative of the principles of the present invention. Other modifications that may be adopted are within the scope of the present invention. Therefore, by way of example, but not as a limitation, alternative configurations of the present invention may be used consistent with the teachings herein. Therefore, the present invention is not limited to what is precisely shown and described.
Claims
1. A methanol reforming catalyst composition comprising: A ZnO phase, present in the composition in an amount of 20-75 wt %; a zinc-aluminum spinel phase, present in the composition in an amount of 20-60% by weight; and The Cu dopant is present in the composition in an amount of 0.1-20 wt %.
2. The catalyst composition of claim 1, wherein the ZnO phase is present in an amount ranging from 30-70 wt%, or 40-60 wt%, or 30-50 wt%.
3. The catalyst composition according to any one of claims 1-2, wherein the ZnO phase has an average crystallite size in the range of 1-50 nm (e.g., 2.5-40 nm, or 5-30 nm).
4. The catalyst composition of any one of claims 1-3, wherein the zinc-aluminum spinel phase is present in the composition in an amount ranging from 30-60 wt%, or 40-60 wt%, or 30-50 wt%.
5. The catalyst composition according to any one of claims 1-4, wherein the zinc-aluminum spinel phase has an average crystallite size in the range of 1-100 nm (e.g., 2.5-75 nm, or 5-50 nm).
6. The catalyst composition according to any one of claims 1 to 5, wherein the Cu dopant is present in the composition in an amount of 0.5-15 wt % (e.g., 1-10 wt %), calculated as CuO.
7. The catalyst composition according to any one of claims 1 to 6, having crystalline Al2O3 in an amount of up to 5 wt%, e.g., up to 4 wt%, or up to 3 wt%, or up to 2 wt%, or up to 1 wt%.
8. A calcined methanol reforming catalyst composition comprising oxides of Zn, Al and Cu, wherein: Zn is present in the composition in a total amount of 40-80 wt % (e.g., 60-80 wt %), calculated as ZnO; Al is present in the composition in a total amount of 20-50 wt % (e.g., 20-40 wt %), calculated as Al2O3; and Cu is present in the composition in a total amount of 0.5-25 wt % (e.g., 1-15 wt %), calculated as CuO, wherein the catalyst composition comprises at least 20 wt % (e.g., at least 30 wt %, or at least 40 wt %) zinc-aluminum spinel as determined by XRD and calculated as ZnAl2O4.
9. The catalyst composition according to any one of claims 1 to 8, further comprising at least one of: Mg, present in an amount of 0.1-2 wt % (e.g., 0.5-1.5 wt %), calculated as MgO; and K, present in an amount of 0.25-3 wt % (e.g., 0.5-2 wt %), calculated as KO.
10. The catalyst composition of any one of claims 1-9, wherein the catalyst composition does not contain more than 15 wt % (e.g., more than 10 wt %) of copper, calculated as CuO, and does not contain more than 1 wt % (e.g., more than 0.5, or more than 0.1 wt %, or more than 0.01 wt %) of chromium, calculated as Cr2O3.
11. The catalyst composition of any one of claims 1 to 10, wherein the total amount of oxides of Cu (calculated as CuO), Al (calculated as Al2O3) and Zn (calculated as ZnO) is at least 90 wt%, e.g., at least 95 wt%, of the catalyst composition.
12. A method for preparing a methanol reforming catalyst composition according to any one of claims 1 to 11, the method comprising: providing a precursor aqueous solution comprising zinc ions, aluminum ions and copper ions; precipitating a solid catalyst precursor comprising zinc, aluminum and copper salts from an aqueous precursor solution; and then The solid catalyst precursor is calcined to provide a catalyst composition.
13. A process for carrying out a methanol reforming reaction comprising contacting a feed comprising water and methanol with a catalyst composition according to any one of claims 1 to 20 or 30 at a temperature of at least 300°C to form hydrogen and carbon dioxide.
14. A process according to claim 13, wherein the feed comprises at least 10 vol% methanol, e.g., at least 20 vol% methanol, and wherein the molar ratio of water to methanol present in the feed is in the range of 0.5-2.5, e.g., 0.5-2.3, or 0.5-2, or 0.5-1.8, or 0.5-1.5, or 0.7-2.5, or 0.7-2.3, or 0.7-2, or 0.7-1.8, or 0.7-1.5, or 1-2.5, or 1-2.3, or 1-2, or 1-1.8, or 1-1.
5.
15. The method of any one of claims 13 and 14, further comprising directing the contacted hydrogen-containing product to a fuel cell.
Citation Information
Patent Citations
Methanol reforming catalyst
US20010021469A1
Catalyst for steam reforming of methanol and method for producing hydrogen therewith
US20020039965A1
Catalyst for methanol reforming, process for producing the same and method for reforming methanol
US5635439A
Methanol steam reforming catalysts
WO2010138483A2